2012
DOI: 10.1111/j.1944-9720.2013.01209.x
|View full text |Cite
|
Sign up to set email alerts
|

Study Abroad, Foreign Language Use, and the Communities Standard

Abstract: Although participation in multilingual communities around the world has been understood to be the raison d'être for foreign language study, the Communities standard has been portrayed as an extracurricular experience and more difficult to weave into instruction than the other standards. This article addresses two questions: (1) Does a study abroad experience facilitate meeting the Communities standard? and (2) How can collegiate foreign language curricula enhance the study abroad experience and fulfillment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 54 publications
(83 reference statements)
0
18
1
1
Order By: Relevance
“…For example, Jackson () described a program in which students are provided pre‐sojourn training in ethnographic techniques of analytic participant‐observation, and Kinginger () proposed a number of language‐based projects designed to facilitate students' interactions with their local hosts. In discussing study abroad in relation to the Communities Standard, Allen and Dupuy () outlined a number of related suggestions, from the use of telecollaborative courses and other social networking resources to link students with peers abroad before and after they go to explicit links between classroom and community in the study abroad curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Jackson () described a program in which students are provided pre‐sojourn training in ethnographic techniques of analytic participant‐observation, and Kinginger () proposed a number of language‐based projects designed to facilitate students' interactions with their local hosts. In discussing study abroad in relation to the Communities Standard, Allen and Dupuy () outlined a number of related suggestions, from the use of telecollaborative courses and other social networking resources to link students with peers abroad before and after they go to explicit links between classroom and community in the study abroad curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…In Julie's view, a TL community was not necessarily determined by social (TL use) practices, but rather by geography-a more traditional notion of what defines community (e.g., Thorne, 2007;contrast with Oguz et al, 2010). In other words, Julie (like many instructors in previous studies, e.g., ACTFL, 2011;Kadish, 2000;McAlpine, 2000;Willis Allen & Dupuy, 2012;Worth, 2006) envisioned a place where the majority of speakers of the language would be native speakers and imagined entering a group of German speakers abroad as the primary means to gain access to a TL community.…”
Section: Communities Based On Native Speaker Status (Types a And C)mentioning
confidence: 97%
“…Results of a survey of 2,134 language educators showed that instructors found the Communities standard to be the hardest to integrate (ACTFL, 2011), primarily due to lack of training, professional development, and resources; the belief that TL communities were "nebulous" (p. 28) and out of their control; and the reality that taking students into the local community or abroad was not typically feasible. Other studies have also found that achieving the aims of the Communities standard (Sarroub & Moeller, 1999;Willis Allen & Dupuy, 2012) or the Communities and Connections standards (Long, 2005) were the most challenging for instructors, that the Communication and Cultures standards were most emphasized in classes (see also ACTFL, 2011), and that the Communities goals received the least emphasis in classes. This is perhaps because the Communities standard is often conceived of in terms of extracurricular activities (Magnan, 2008, Willis Allen & Dupuy, 2012e.g., Lally, 2000;McAlpine, 2000;Overfield, 1997;Phillips, 1998;Weldon & Trautmann, 2003).…”
Section: Perspectives On Communitiesmentioning
confidence: 99%
See 2 more Smart Citations